Penentuan Nilai Emisivitas Warna Menggunakan Penerangan pada Miniatur Ruang Berbentuk Kubus - Cariti Dassa Urra (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study using a cuboidal space miniature aims to determine the emissivity values ​​of purple, green, and blue colors. By carrying out eight actions to change the power of the lamp, starting from incandescent lamps of 5 watts, 25 watts, 60 watts, 75 watts, 100 watts and 5 watts, 20 watts, and 25 watts of white TL lamps. Emissivity value can be calculated by comparing the value of the resistance of each color to the value of black resistance. The results show that the emissivity value of purple (purple comet) is 0.91, emissivity of green (going green) is 0.84, and emissivity of blue (true) blue) of 0.77.